2010
DOI: 10.1093/heapro/daq032
|View full text |Cite
|
Sign up to set email alerts
|

Developing and evaluating a relevant and feasible instrument for measuring health literacy of Canadian high school students

Abstract: Health literacy has come to play a critical role in health education and promotion, yet it is poorly understood in adolescents and few measurement tools exist. Standardized instruments to measure health literacy in adults assume it to be a derivative of general literacy. This paper reports on the development and the early-stage validation of a health literacy tool for high school students that measured skills to understand and evaluate health information. A systematic process was used to develop, score and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 15 publications
6
128
1
5
Order By: Relevance
“…As such it adds a particular perspective, which, however, does not cover HL in the broader form that we have addressed in the present study. The Wu et al (Wu et al, 2010) study is closer to our focus. The authors developed a broader HL measurement tool for high school students and found it feasible for classroom use.…”
Section: Summary and Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…As such it adds a particular perspective, which, however, does not cover HL in the broader form that we have addressed in the present study. The Wu et al (Wu et al, 2010) study is closer to our focus. The authors developed a broader HL measurement tool for high school students and found it feasible for classroom use.…”
Section: Summary and Discussionmentioning
confidence: 64%
“…(Levin-Zamir et al, 2011)], education [expecting it to be positively associated with HL; see e.g. (Wu et al, 2010 andLevin-Zamir et al, 2011)] and a value-based item measuring the importance of a healthy lifestyle [ plausibility would suggest a positive association with HL; see also (Schmidt et al, 2010)]. Anticipated associations were investigated using one-way analysis of variance (ANOVA) with a Bonferroni correction Health literacy among young adults 727 as post hoc procedure to compare the significance of differences in mean scores according to education and health value.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies point to better functional health literacy for women (12,16,19) . Only one study (11) indicated better functional health literacy in men and associated this finding with the lower educational level of the women who took part.…”
Section: Discussionmentioning
confidence: 99%
“…Os rapazes afirmam receber mais informação acerca deste tema do que as raparigas (Ackard & Neumark-Sztainer, 2001, Al-Qallaf, Al-Otaibi, & Othman, 2012e Kwan et al, 2010. Apesar da informação recebida acerca dos vários tópi-cos em saúde, os níveis baixos de literacia em saúde nos adolescentes rondam os 10 a 40% (Sanders, Federico, Klass, Abrams, & Dreyer, 2009), sendo os níveis de literacia em saúde superiores no sexo feminino, e nos jovens com nacionalidade, naturalidade ou língua estrangeira (Wu, et al, 2010).…”
Section: Objetivo(s)unclassified